Healthy Living: Changing Your Lifestyle to Improve Your Blood Pressure - Karla P. Shelnutt (EDIS, 2009)
FCS8885, a 2-page illustrated fact sheet by Karla P. Shelnutt, highlights some lifestyle changes that can help control or prevent high blood pressure — losing weight, increasing physical activity, limiting alcohol consumption, and stopping smoking. Published by the UF Department of Family Youth and Community Sciences, October 2009.